Decompressive hemicraniectomy in the management of subcortical spontaneous intracerebral hemorrhage. (2nd October 2020) - Iwuchukwu, Ifeanyi; Bui, Cuoung; Hsieh, Billie; Sabharwal, Vivek; Mohammed, Alaa; McGrade, Harold; Biro, Erin; Nguyen, Doan; Sulaiman, Olawale
Abstract: Background: The benefit of decompressive hemicraniectomy in patients with malignant acute ischemic stroke is well established, however its role in supratentorial intracerebral hemorrhages is unclear and evolving. Prior studies combined cortical and subcortical hemorrhages in their analysis despite their different natural history. Subcortical hematoma is associated with worse outcomes due to mechanical compression of subcortical structures. We describe outcomes of a matched comparison of patients with spontaneous subcortical hemorrhage managed with hemicraniectomy versus medical management alone. Methods: Using our "Get-with-the-guideline stroke" database, patients with spontaneous subcortical hematoma managed with hemicraniectomy were identified. Using age, gender, and hematoma volume (categorized as 0–30, 30–60, >60ml), patients managed with hemicraniectomy were matched with medical management alone. Outcomes included hospital length of stay, discharge disposition, and Glasgow outcome score. Results: Eight patients with subcortical hematoma managed with hemicraniectomy were matched with 22 medically managed patients. Other than use of antithrombotics, clinical characteristics did not differ between groups. On comparing outcomes, hospital length of stay in the hemicraniectomy group (26.5 vs 12.5 days p = 0.006) was significantly longer. Discharge disposition did not differ between groups (75% vs 36.4% p = 0.101). Despite a higher frequency of Glasgow outcome score ≥ 3 at 90 days amongst hemicraniectomy cases, there was no significant difference between groups (71.3% vs 54.5% p = 0.535). Conclusion: Hemicraniectomy for subcortical hematoma was associated with a prolonged hospital stay. Despite improving survival and favorable discharge disposition, there was no statistically significant difference between groups. Further studies on the benefit of hemicraniectomy in subcortical hematoma are needed.